2018
DOI: 10.1007/s11845-018-1781-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of diagnostic performance of vacuum-assisted biopsy and core needle biopsy for breast microcalcification: a systematic review and meta-analysis

Abstract: Compared with CNB, VAB shows better diagnostic performance in DCIS underestimation rate and microcalcification retrieval rate. However, CNB shows a significantly lower complication rate. More studies are needed to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Furthermore, it has been reported that the learning curve time of VABB (4 weeks) is shorter than that of CNB (12 weeks) (16), and that there is a greater amount of tissue removed. Also, US-guided localization surgery is more suitable for in situ cancers, invasive cancers which need neoadjuvant therapy and more accurate evaluation of neoadjuvant therapy response (17)(18)(19)(20)(21). Compared to the negative predictive value and false negative rate of open surgical biopsy (99.61% and 4.76%), the negative predictive value of VABB was 99.77% and the false negative rate was 0.96% (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that the learning curve time of VABB (4 weeks) is shorter than that of CNB (12 weeks) (16), and that there is a greater amount of tissue removed. Also, US-guided localization surgery is more suitable for in situ cancers, invasive cancers which need neoadjuvant therapy and more accurate evaluation of neoadjuvant therapy response (17)(18)(19)(20)(21). Compared to the negative predictive value and false negative rate of open surgical biopsy (99.61% and 4.76%), the negative predictive value of VABB was 99.77% and the false negative rate was 0.96% (22).…”
Section: Discussionmentioning
confidence: 99%
“…An adequate amount tissue significantly affects the diagnostic accordance rate [ 6 , 18 ]. Therefore, vacuum-assisted biopsy has a higher diagnostic accuracy rate and better safety, when compared to core needle biopsy [ 5 ]. Accurate preoperative diagnosis is essential for treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuum-assisted Mammotome biopsy can obtain sufficient samples without repeated puncture. Hence, the diagnostic accuracy is high [ 5 , 6 ]. However, it requires expensive special equipment (vacuum pumps, operating handles, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The vacuum system and larger gauge needles are associated with higher-quality samples, while the greater volume of tissue collected by VAB minimizes sampling error and compensates sampling error due to patient movement or due to deep injection of anesthetic. A recent meta-analysis has shown that VAB is related to lower Ductal carcinoma in situ (DCIS) underestimation rate compared to CNB (22.98% by CNB and 11.05% by VAB, p < 0.001) with higher rates of calcification retrieval (RR = 0.89, 95% CI 0.81 to 0.98, p = 0.02) [19]. The sensitivity and negative predictive value of VAB have been reported as high as >99% in a large retrospective study [17].…”
Section: Mammography-guided Biopsymentioning
confidence: 99%